Influence of Photoperiod on Lipid, Protein and Astaxanthin Content of Cystic Haematococcus pluvialis Cultivated in High-Concentration Molasses Medium - Şimşek, Gökçe Kendirlioğlu; Çetin, A. Kadri (Uğur ÇAKILCIOĞLU, 2025)
This study investigates the response of Haematococcus pluvialis to controlled induction of the cyst stage using a high-carbon molasses medium and evaluates how distinct photoperiod regimes (16L/8D, 12L/12D, 8L/16D, 4L/20D, and 24D) regulate cell development and metabolite accumulation. The applying of molasses at 8 g/L effectively reduced light penetration and generated a carbon-rich stress environment, accelerating encystment and promoting the activation of metabolic pathways associated with astaxanthin, protein and lipid enrichment. Growth analyses indicated that the 16L/8D treatment supported the highest cell density even under cyst-inducing conditions, highlighting the stimulatory role of extended illumination. Protein formation was maximized under this regime, reaching 2.409 µg/mL on day 10, whereas the 12L/12D cycle provided the strongest stimulation for astaxanthin synthesis, with a peak value of 2.997 µg/mL. Lipid levels followed a similar pattern, with the most highest accumulation (65.9%) observed under long-light conditions, while continuous darkness markedly suppressed all metabolic outputs. Correlation mapping revealed that the photoperiod exerted a coordinated regulatory influence on growth, astaxanthin, protein, and lipid production, indicating an integrated metabolic adjustment to light–dark cycling during the cyst phase. Overall, the findings demonstrate that molasses is a low-cost and efficient substrate for inducing the red/cyst stage and that optimizing of photoperiod conditions can substantially enhance the biosynthesis of high-value metabolites. These results provide a promising framework for cost-effective and environmentally sustainable production strategies in astaxanthin biotechnology, functional food development, nutraceutical formulations, and microalgae-based biofuel applications.
Keywords: Botany (Other); Bitki Bilimi (Diğer)